2021
DOI: 10.11648/j.ijrse.20211001.12
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Testing of an Organic Rankine Cycle Designed for Exhaust Heat Recovery Applications in Truck Engines

Abstract: The transport sector is presently accountable for 1/4 of total greenhouse gas released to the atmosphere, with road transportation depicting 17.8% of the total transport emissions contributing to global warming's growing threats caused by the continuous release of exhausting gases from internal combustion engines (ICEs). These exhaust threats call for improved sustainable ways of deploying fossil fuel in an environmentally friendly manner. Many sustainable solutions have been suggested recently with others alr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Because of its simplicity and ability to recover energy more effectively from low-to mediumgrade heat sources, the ORC (organic Rankine cycle) has been the most investigated WHR technology recently. Due to the quality of heat obtainable in the exhaust gas of vehicle internal combustion engines (ICEs), studies have shown that the ORC system has an immense possibility for successful exhaust heat recovery (EHR) application in the transportation sector [8][9][10][11][12]. The ORC system works the same way as the steam Rankine cycle but uses organic compounds as working fluids instead of the water found in the traditional Rankine cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its simplicity and ability to recover energy more effectively from low-to mediumgrade heat sources, the ORC (organic Rankine cycle) has been the most investigated WHR technology recently. Due to the quality of heat obtainable in the exhaust gas of vehicle internal combustion engines (ICEs), studies have shown that the ORC system has an immense possibility for successful exhaust heat recovery (EHR) application in the transportation sector [8][9][10][11][12]. The ORC system works the same way as the steam Rankine cycle but uses organic compounds as working fluids instead of the water found in the traditional Rankine cycle.…”
Section: Introductionmentioning
confidence: 99%